SOLVING OF INVERSE PROBLEM OF THEORY OF DISTRIBUTING VALUES FOR WHOLE CURVES - Овчар, Ігор Євгенійович; Савчук, Ярослав Іванович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
At insignificant limitation the decision of reverse task of theory of distributing of values is resulted for the whole curves of endless order.